An examination of the relationship between various mental health problems and the three sub factors of the Rutgers Alcohol Problem Index - Mendez, Marcos (Kansas State University, 2009)
The Rutgers Alcohol Problem Index (RAPI) is a well-known instrument used as a primary outcome measure in intervention studies with college students. It has been used in studies assessing the developmental trajectory of high-risk drinking and also used in studies which address the predictors of alcohol-related problems among college students (Carey & Correia, 1997; Ham & Hope, 2005; Levy & Earleywine, 2003). Martens et al. (2006) found that the RAPI individual items were able to be grouped in three distinct subfactors (Abuse/Dependence, Personal Consequences, and Social Consequences). The objective of this study was to examine the relationship between various mental health problems (depression, posttraumatic stress disorder, physical abuse victimization, physical abuse perpetration, sexual coercion victimization, sexual coercion perpetration, and self-esteem) and the three subscales of the RAPI. It was anticipated that the mental health problems explain more of the variance on Abuse/Dependence than on Personal or Social Consequences. Results indicated that even though mental health problems explain more of the variance on Abuse/Dependence than on Personal or Social Consequences, the difference did not appear large enough to suggest that the subfactors represent unique domains. In conclusion, it cannot be assumed that the three subfactors measure distinct and exclusive types of consequences. A student that scores high on Abuse/Dependence also may be experiencing Personal and Social Consequences.
Keywords: Rutgers Alcohol Problem Index; Mental health problems; Psychology, Clinical (0622)